The relationship between accounting students’ moral development and narcissism on academic fraud - Nujmatul Laily; Ria Zulkha Ermayda; Aulia Azzardina (Journal of Education and Learning (EduLearn), 2021)
The stages in an individual's moral development will determine how an individual will behave. Kohlberg divides moral development into three stages, namely pre-conventional, conventional and post-conventional. However, the stages of individual moral development may vary. These different levels of moral development will influence individuals’ behavior when they face ethical dilemmas. This research aimed to determine the correlation between accounting students’ moral development and narcissism on academic fraud. This quantitative research employed a survey method. The research samples were 46 accounting students taken with a random sampling method. The results showed that narcissism affects accounting students’ academic fraud but there is no correlation between the level of moral development and academic fraud.